A systematic analysis of the global and regional burden of colon and rectum cancer and the difference between early- and late-onset CRC from 1990 to 2019 - Li, Liu-Bo; Wang, Li-Yu; Chen, Da-Ming; Liu, Ying-Xia; Zhang, Yuan-Hui; Song, Wei-Xiang; Shen, Xu-Bo; Fang, Sheng-Quan; Ma, Zheng-Yuan (Frontiers in Oncology, 2023)
The disease burden of colorectal cancer (CRC) varies greatly in different geographical locations, however there was no further quantitative analysis of regional social development and the disease burden of CRC. In addition, the incidence of early- and late-onset CRC had increased rapidly in developed and developing regions, respectively. The main purpose of this study was to investigate the trend of disease burden on CRC in different regions and the epidemiological differences of early and late-onset CRC and their risk factors. In this study, estimated annual percentage change (EAPC) was employed to quantify trends in age-standardized rate of incidence (ASIR), mortality, and disability-adjusted life-years. Restricted cubic spline model was implemented to quantitative analyze the relationship between the trend of ASIR and Human development index (HDI). In addition, the epidemiological characteristics of early- and late-onset CRC was investigated through a stratified analysis of age groups and different regions. Specially, meat consumption and antimicrobial usage was included to explore the differences in risk factors on early- and later-onset CRC. Through quantitative analysis, it is founded that ASIR of CRC was exponentially positive correlation with the HDI 2019 in different regions. And the growing trend of ASIR in recent years showed different characters in different-leveled HDI region. Specially, ASIR of CRC showed significant growth in developing countries, while it remains stable or falling in developed countries. Moreover, linear correlation was found in ASIR of CRC with meat consumption in different regions, especially in developing countries. And similar correlation relationship between the ASIR and antibiotics usage was found in all age groups with different correlation coefficient in early-onset and late-onset CRC. It is worth mentioning that the early onset of CRC could be attributable to the unrestrained usage of antibiotics in the young age groups of the developed world. To sum up, for better prevention and control CRC, government should pay attention to advocate self-testing and hospital visits among all age group, especially young people with high risk of CRC, and strictly control the meat consumption and the usage of antibiotics.